Crying out in pain—A systematic review into the validity of vocalization as an indicator for pain. (13th July 2020) - Helmer, Loreine M.L.; Weijenberg, Roxane A.F.; de Vries, Ralph; Achterberg, Wilco P.; Lautenbacher, Stefan; Sampson, Elizabeth L.; Lobbezoo, Frank
Abstract: Background: Vocalization is often used to assess pain, sometimes combined with other behaviours such as facial expressions. Contrary to facial expressions, however, for vocalization, there is little evidence available on the association with pain. The aim of this systematic review was to critically analyse the association between vocalization and pain, to explore if vocalizations can be used as a "stand‐alone" indicator for pain. Methods: The search was performed according to the Prisma Guidelines for systematic reviews and meta‐analysis. The following terms were used: "Pain Measurement, " "Vocalization" and "Verbalization." The study population included verbal and non‐verbal individuals, including older people and children. The search was performed in three different databases: PubMed, Embase and CINAHL. A total of 35 studies were selected for detailed investigation. Quality assessments were made using two grading systems: Grading of Recommendations Assessment Development and Evaluation system and the Newcastle‐Ottawa scale. Results: An association between vocalization and pain was found in most studies, particularly when different types of vocalizations were included in the investigation. Different types of vocalization, but also different types of pain, shape this association. The association is observed within all groups of individuals, although age, amongst others, may have an influence on preferred type of vocalization. Conclusions: There is an association between vocalization and pain. However, vocalization as a "stand‐alone" indicator for pain indicates only a limited aspect of this multifactorial phenomenon. Using vocalization as an indicator for pain may be more reliable if other pain indicators are also taken into account. Significance: Vocalizations are frequently used in pain scales, although not yet thoroughly investigated as a "single indicator" for pain, like, e.g. facial expression. This review confirms the role of vocalizations in pain scales, and stresses that vocalizations might be more reliable if used in combination with other pain indicators.